Kajian Terhadap Bentuk Visual Elemen Interior Grand Inna Medan Medan - Hermita, Rani; Fahrezi, Thasya Choiriani (CandraRupa : Journal of Art, Design, and Media, 2025)
The Grand Inna Medan Hotel is a legacy of the Dutch East Indies era which has historical value and is one of the heritages in the city of Medan which, along with the development of the times, was built while maintaining the Dutch design nuances combined with Malay. This research discusses how the visual form of the Grand Inna Medan interior in Medan is related to design aspects. The method used in this research is descriptive qualitative. The results obtained from this research are what the interior of the Grand Inna Medan building looks like, which consists of hotel rooms, meeting hall, lobby and restaurant. The interior design of Grand Inna Medan's rooms, restaurants and meeting rooms takes Malay and Dutch colonial concepts. Each room has walls, floors and ceilings that carry Dutch colonial and Malay colonial concepts. Floor materials using different colors and floor shapes create diversity in the room. The patterns on the walls are symmetrical and use different colors to create an impression of harmony and blend with the color of the floor. The color of the doors and windows is described according to the theme of each room in addition to supporting its main function as lighting circulation. The colors used on the ceiling of the room are colors that can raise a person's mood and enthusiasm. The different levels of each room create a variety of shapes and room harmony.